Comparative evaluation of midline versus parasagittal interlaminar epidural steroid injection for management of symptomatic lumbar intervertebral disc herniation - Amit Kumar; Naveen Malhotra; Aditi; Jyotsna; Anshul; Disha Gupta (Indian Journal of Anaesthesia, 2022)
Background and Aims: Epidural steroid injections (ESIs) with or without local anaesthetics have been used for the past several years for the treatment of back pain, especially for radicular symptoms. The aim of this prospective study was to compare the efficacy of midline with parasagittal approach for interlaminar ESI in the management of symptomatic lumbar intervertebral disc herniation. Methods: Sixty patients (aged 20–60 years) with pain pattern consistent with lumbar radiculopathy caused by lumbar intervertebral disc herniation and who did not respond to conservative treatment were included in the study. They were randomly divided in two groups of 30 each: group I (MILESI, n = 30) consisting of midline interlaminar ESI, and group II (PSILESI, n = 30) consisting of parasagittal interlaminar ESI. They were administered a combination of 80 mg of methylprednisolone acetate (40 mg/ml) and 6 ml of 0.25% bupivacaine (total volume of 8 ml). Pain, patient satisfaction, and the Oswestry Disability Index (ODI) were assessed at different time intervals before and after the procedure for up to six months. Results: The improvement in pain score after ESI was statistically significant in both the groups at all intervals of time, with no significant difference between the two groups. The mean pain score was <3 from two weeks onwards after the injection. The pain score decreased by more than five points and it was around two points at the end of the six-month study period. Around 50% of patients in both groups had excellent satisfaction. Conclusion: Both techniques were effective in providing good analgesia. Pain relief and improvement in disability were clinically better with the parasagittal interlaminar approach.